A Narrative-Based Case Study of Language Learning Investment and L2 Identities in the Pakistani EFL Context - Mariam, Saba; Malik, Moazzam Ali (Annals of Human and Social Sciences, 2024)
The present study explores how a language learner is inextricably connected with the social world and how the learners invest in negotiating power relations to achieve their L2 identity. The study draws insights from Darvin and Norton’s Investment Model (2015) to unearth how investment contributes to the development of L2 learners’ identity in the Pakistani EFL context. The data were collected from two Pakistani EFL learners with the help of face-to-face interviews. The findings show that investment plays an important role in identity formation which is boosted by other power networks. Furthermore, the data show that the components of the investment model are individually important to support the process of learning and identity formation of EFL learners.